Factors associated with delirium and cognitive decline following hip fracture surgery. (1st December 2020) - Uzoigwe, Chika E.; O'Leary, Lawrence; Nduka, Jude; Sharma, Daman; Melling, David; Simmons, Damon; Barton, Simon
Abstract : Aims: Postoperative delirium (POD) and postoperative cognitive decline (POCD) are common surgical complications. In the UK, the Best Practice Tariff incentivizes the screening of delirium in patients with hip fracture. Further, a National Hip Fracture Database (NHFD) performance indicator is the reduction in the incidence of POD. To aid in its recognition, we sought to determine factors associated with POD and POCD in patients with hip fractures. Methods: We interrogated the NHFD data on patients presenting with hip fractures to our institution from 2016 to 2018. POD was determined using the 4AT score, as recommended by the NHFD and UK Department of Health. POCD was defined as a decline in Abbreviated Mental Test Score (AMTS) of two or greater. Using logistic regression, we adjusted for covariates to identify factors associated with POD and POCD. Results: Of the 1, 224 patients presenting in the study period, 1, 023 had complete datasets for final analysis. POD was observed in 242 patients (25%). On multivariate analysis only preoperative AMTS and American Society of Anesthesiologists grade (ASA) were independent predictors of POD. Every point increase in AMTS was associated with a fall in the odds of POD by a factor of 0.60 (95% confidence interval (CI) 0.56 to 0.63, p < 0.001). Every grade increase in ASA led to a 1.7-fold increase in the odds of POD (95% CI 1.13 to 2.50, p = 0.009). A preoperative AMTS of less than 8 was strongly predictive of POD with area under the receiver operating characteristic of 0.86 (95% CI 0.84 to 0.89). Only ASA was predictive of POCD—every grade increase in ASA led to a 2.6-fold increase in the odds of POCD (95% CI 1.7 to 4.0, p < 0.001). Conclusion: POD and POCD are common in the hip fracture patients. Preoperative AMTS and ASA are strong predictors of POD, and ASA predictive of POCD. This may aid in the earlier identification of those most at risk and suited for the patient consent and decision-making process. Cite this article: Bone Joint J 2020;102-B(12):1675–1681.